Case Report: First report of a Wilms tumor in an individual with Dias–Logan syndrome (BCL11A-related intellectual disability) - Troullioud Lucas, Alexandre G.; Fiala, Elise; Razeq, Ahmed; Sauerhaft, Talia; Price, Anita P.; Mosquera, Juan Miguel; Miyauchi, Jeremy; Gao, Ming; Walsh, Michael F.; Ortiz, Michael V. (Frontiers in Oncology, 2025)
Dias–Logan syndrome (DLS) is a rare condition caused by heterozygous germline BCL11A pathogenic variants associated with global developmental delay, distinctive facial features, and asymptomatic persistence of fetal hemoglobin. There has been no evidence of an association between DLS and increased risk of cancer. We report the first instance of a child with DLS diagnosed with cancer, a Wilms tumor (WT), who is notably much older than the typical onset. Although this case alone is insufficient to warrant routine WT screening in DLS, given the extreme rarity, we cannot rule out an association with DLS and WT predisposition.